ANALISA PENGARUH CORPORATE SOCIAL RESPONBILITY, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN SUB SEKTOR PERKEBUNAN YANG TERDAFTAR DIBURSA EFEK INDONESIA TAHUN 2015-2019 - Renika Hasibuan; Owen De Pinto Simajuntak (Universitas Methodist Indonesia, 2022)
This study aims to examine the effect of Corporate Social Responsibility (CSR), firm size, and profitability on corporate tax aggressiveness. The independent variables used in this study are the disclosure of corporate social responsibility, company size, and profitability, while the dependent variable in this study is tax aggressiveness as measured by the effective tax rate (ETR). The population in this study amounted to 18 plantation sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2019 period. Determination of the research sample using purposive sampling and obtaining a sample of 12 plantation companies based on certain criteria. The results showed that simultaneously, CSR, company size, and profitability had no effect on tax aggressiveness, while partially, company size and profitability had no effect on tax aggressiveness, while CSR variable had a significant effect on tax aggressiveness in sub-plantation companies listed in Indonesia stock exchange.